Rural Women Who Undertake and Empower Themselves: Comparative Analysis in Communities in Mexico - Hector Manuel Villanueva Lendechy; Ivonne Tapia Villagómez (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This research presented a comparative analysis of 4 original and qualitative studies that were carried out in 2018 and 2019, in the Mexican companies Taselotzin, Artemali and in El PIRA Hermanos, located in the state of Puebal and a women´s venture in the community of Samaria in the state of Veracruz. In these investigations, the relationship between the variables was identified: social entrepreneurship and empowerment of rural women. The method used in the investigations was inductive and the techniques were documentary and panel interview in situ, the categories of analysis of the previous research: self-own business, decision making for the community, training, learning, culture ande sustainability. It was concluded that the 4 ventures are prone to training, which contributed to organizational learning and innovation, and in turn, to make the Company more competitive. In addition, Taselotzin opposed the construction of the High Voltage line in Cuetzalan, Artemali participated in health campaigns, moderately collects its raw material and takes care of the forest from the depredation of its resources. The PIRA Brothers regulate the activity of pyrotechnics at the state level to avoid accidents that become tatal and the farmers of Samaria pratice organic agricultura.